Conflicts through the lens of Chinese war photojournalists - Zhang, Shixin Ivy (Intellect, 2015)
Since the 1990s, China, as a new global power, has played an increasing role in international affairs. Chinese journalists have travelled to war and conflict zones overseas to report and file news coverage back home. This article surveys the historical development of Chinese war photography. It also critically examines the ideology and practices of four young Chinese photojournalists who work at a Chinese state news agency through semi-structured interviews and analysis of the photographs they took in conflict zones. The author argues that contemporary Chinese war photojournalists take realism as their main aesthetic and ideological doctrine in a sense to provide visual evidences and to stress the naturalism and symbolic power of war images. The visual representations of civilians’ sufferings and hope for peace correspond with China's peaceful diplomatic policy and non-intervention principles. The war images elicit sympathetic public emotions and collective memory in China. Chinese photojournalists’ depictions of wars and conflicts are influenced by internal political, organizational and individual constraints as well as the changing nature of contemporary wars.